2009
DOI: 10.1097/ico.0b013e318182ecf9
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Preservative-Free Topical Anesthetic Drops in Current Use in Ophthalmology Departments

Abstract: Currently used preservative-free topical anesthetics differ in bacterial growth inhibition. This in vitro study showed that proxymetacaine 0.5% is the least inhibitory on bacterial growth and therefore the most appropriate to be used before corneal scrapes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 9 publications
1
27
0
1
Order By: Relevance
“…Previous publications reported that certain local anesthetic eye drops had strong antimicrobial effects, which were dose-related and related to whether the drops contained preservatives (Mullin and Rubinfeld, 1997; Dantas et al, 2000; Pelosini et al, 2009). Compared to published results, we detected a relatively lower incidence of conjunctival flora in present study, and the use of local anesthetic might be contributory.…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications reported that certain local anesthetic eye drops had strong antimicrobial effects, which were dose-related and related to whether the drops contained preservatives (Mullin and Rubinfeld, 1997; Dantas et al, 2000; Pelosini et al, 2009). Compared to published results, we detected a relatively lower incidence of conjunctival flora in present study, and the use of local anesthetic might be contributory.…”
Section: Discussionmentioning
confidence: 99%
“…Its disinfectant properties are alleged to be one reason topical anesthetics might be expected to alter culture results. However, an in vitro study revealed that preservative‐free proxymetacaine reduced growth of Staphylococcus epidermidis and that preservative‐free 1% tetracaine along with 4% oxybuprocaine‐inhibited S. epidermidis , S. aureus , P. aeruginosa , and Streptococcus pneumoniae growth . Therefore, it appears that preservatives may not be the sole cause for inhibition; and that, the anesthetic agents themselves may exert a direct antibacterial action.…”
Section: Discussionmentioning
confidence: 99%
“…Atopic dogs had significantly more frequent positive bacterial cytology (85.7 versus 52.4%) and cultures (57.1 versus 14.3%) than healthy dogs. The lower frequency of positive cultures could be explained in part by double sampling from the same conjunctival sac and by the use of the preservative‐free topical anaesthetic solution, as 0.4% oxybuprocaine hydrochloride was recently reported to exert an antibacterial effect in vitro 41 . As the same topical anaesthetic solution was used in both groups of dogs, the statistical evaluation of the differences between the two groups should not have been affected.…”
Section: Discussionmentioning
confidence: 99%